AGAINST THE ORDER OF NAZIIN BRIAN SINGER'S VALKYRIE MOVIE (2008):AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Irsanianto, Nur Rhohmad (2012)
SUMMARY NUR REOEMAD IRSANIANTO. A 320 060 094. AGAINST THE ORDER OF NAZI IN BRIAN SINGER'S VALKYRIE MOVIE (2008): AN INDIVIDUAI, PSYCEOLOGICAL APPROACE. R.ESEARCS PAPER MUHAMMADIYAH UNTVf,RSITY OF SURAKAR'TA. 2012. This researchp aperi s aimedt o show againstt he order of nazi in Brian Sirger's Valkyrie movie by using through individual psychological approach. The objectiveso fthe researcha re to analyzet he structurale lementso fthe novel and to analyzeth en ovelb asedo n individuapl sychologicaple rspective. The research is conducted by using qualitative method. The writer uses two data sourcesn amelyp rimary and secondaryd ata source.T he primary data sources of the study arc VdllEfie movie direated by Bryan Singer and the script movre written by Christopher McQuarrie and Nathan Alexander. The secondary data sourcei s taken fiom other referentiald ata. which have relation with research.t he underlying theory and other materials concem to the analysis. It can be from books and internet. The method of the data collection is library research. The techniqueo f data analysisi s descriptivea nalysis. The result ofthe resea.ch is as follows: first, based o1l the structural analysis of each elements,i t shows that the charactera nd charactedzationc, asting,p lot, setting,p oilt of view, lhelIrc, mise-en-scenec,i nematographys, ound,a nd editing are rclated to each other ard form the unity into good quality of a movie. Second, the individual psychologicala nalysiss howst hat the strivingo f superioritya gainstth e ordero f nazi of ColonelS tauffenbercga nb e an effort to makeb etterf uturel ife for hrs familya ndG erman'sp eople. .